Evighedens frø: - H.C. Andersen og kristendommen - de Mylius, Johan (Kirkehistoriske Samlinger, 2005)
The seed of eternity - Hans Christian Andersen and Christianity Whether or not Hans Christian Andersen may be categorized as a true Christian, as an author and as a person, is a rather complex question. Categories such as rationalism, pantheism, popular superstition, simple childish belief and genuine heartfelt Christianity have all been used to characterize Andersen and his works. Let it also be mentioned, that professional readers of recent decades have found, that he is an encouraging example of true nihilism! Andersen did not share central dogmas of the Lutheran church and did certainly not meet the demands of postwar (Danish) theologians. But his Christianity should not be measured by 2O.th century standards. Like the contemporary authority - maljudged by Kierkegaard, but a highly relevant figure when it comes to 19.th century Christianity - the head of the Danish church, bishop J.P. Mynster, Andersen took his stand in man’s desire for God and for eternity, and over and over again he wrote about the soul being on an eternal journey from darkness towards the light.